Parathyroid hormone therapy improves MRSA-infected fracture healing in a murine diabetic model - Kwon, Hyuk-Kwon; Cahill, Sean V.; Yu, Kristin E.; Alder, Kareme D.; Dussik, Christopher M.; Jeong, Jain; Back, Jung Ho; Lee, Francis Y. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Diabetes mellitus (DM) impairs fracture healing and is associated with susceptibility to infection, which further inhibits fracture healing. While intermittent parathyroid hormone (1-34) (iPTH) effectively improves fracture healing, it is unknown whether infection-associated impaired fracture healing can be rescued with PTH (teriparatide). Methods A chronic diet-induced type 2 diabetic mouse model was used to yield mice with decreased glucose tolerance and increased blood glucose levels compared to lean-fed controls. Methicillin-resistant Staphylococcus aureus (MRSA) was inoculated in a surgical tibia fracture model to simulate infected fracture, after which mice were treated with a combination of antibiotics and adjunctive teriparatide treatment. Fracture healing was assessed by Radiographic Union Scale in Tibial Fractures (RUST), micro-computed tomography (μCT), biomechanical testing, and histology. Results RUST score was significantly poorer in diabetic mice compared to their lean nondiabetic counterparts. There were concomitant reductions in micro-computed tomography (μCT) parameters of callus architecture including bone volume/total volume, trabecular thickness, and total mineral density in type 2 diabetes mellitus (T2DM) mice. Biomechanicaltesting of fractured femora demonstrated diminished torsional rigidity, stiffness, and toughness to max torque. Adjuvant teriparatide treatment with systemic antibiotic therapy improved numerous parameters of bone microarchitecture bone volume, increased connectivity density, and increased trabecular number in both the lean and T2DM group. Despite the observation that poor fracture healing in T2DM mice was further impaired by MRSA infection, adjuvant iPTH treatment significantly improved fracture healing compared to antibiotic treatment alone in infected T2DM fractures. Discussion Our results suggest that teriparatide may constitute a viable adjuvant therapeutic agent to improve bony union and bone microarchitecture to prevent the development of septic nonunion under diabetic conditions.